Implementasi Digital Marketing Usaha AccBosku - Trias Abu Salam; Valentino Aris; Muhammad Jamil (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study was motivated by the increasing need for culinary MSMEs to adapt to digital technology development and changing consumer behavior, particularly the growing use of social media and online food delivery services. AccBosku, a culinary business offering crispy chicken with various dipping sauces, still relied on conventional promotion and faced limited market reach due to the absence of structured digital marketing. This study aimed to design and implement digital marketing through Instagram integrated with the GrabFood on-demand service and to analyze its impact on AccBosku’s sales effectiveness. The research used a Research and Development (R&D) method with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through observation, interviews, documentation, and sales records before and after implementation. The results show that digital marketing through Instagram visual content, scheduled posting, GrabFood integration, and Google Maps support improved product visibility, ordering accessibility, and sales performance. Sales increased from an average of 647.5 portions to 1,200 portions after implementation. Therefore, digital marketing is important for expanding promotion, improving customer access, and supporting the growth of culinary MSMEs effectively.